(untitled) (Advancements in Homeopathic Research, 2024)
Chronic sinusitis is a prevalent condition that significantly impacts quality of life. Conventional treatments often provide limited relief, prompting patients to seek alternative therapies. Homeopathy, with its holistic approach, offers a promising option for managing chronic sinusitis. This study aims to evaluate the efficacy of constitutional homeopathic remedies and Mentholum in addressing this condition. Methods A retrospective study was conducted to analyze case reports of patients diagnosed with chronic sinusitis at Sivaraj Homoeopathic Medical College & Research Institute. Patients were categorized into two groups: Group I (constitutional treatment) and Group II (Mentholum 6CH treatment). The clinical course and outcomes of both groups were assessed over a six month period. Results Both groups showed significant improvement in symptoms. In Group I, 46% of patients experienced mild improvement, and 41% experienced marked improvement. In Group II, 34% of patients experienced mild improvement, and 53% experienced marked improvement. No statistically significant difference was observed between the two groups in terms of overall improvement. Conclusion This study suggests that both constitutional homeopathic remedies and Mentholum can be effective in managing chronic sinusitis. Further research with larger sample sizes and randomized controlled trials is warranted to validate these findings and establish the long-term efficacy of these approaches.